Peningkatan Kualitas Hidup Lansia Dengan Husnul Khatimah Care (Hukho Care) - Boy, Elman; Nuralita, Nanda Sari (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2019)
The elderly people’s lifetime requires attentions, especially those related to the health in order that healthy and joyful lifestyle could be achieved. Healthy and joyful life quality for elderly people is expected to bring improvement towards life expectancy. Therefore, effort in improving the life quality of elderly people needs to be taken into account. The implementation of community service program, particularly the one addressed to the elderly people aims to: 1) perform the selection of cognitive function and elderly people’s mood situation; and 2) follow up the selection results. The implementation method was conducted step-by-step, which was through the selection of cognitive function and elderly people’s mood situation using Abbreviated Mental Test (AMT), whereas Workshop Husnul Khatimah Care (Hukho Care) was implemented for the selection results follow-up. AMT was used to measure the psychological condition and memory disorders; it was implemented through interview given to each of the elderly people. The Workshop Hukho Care was conducted through education as well as small and big group discussion. The result shows that 9% of the elderly people suffer from depression, 19% unstable, and 27% suffer from moderate memory disorder. Those who suffer from depression, psychologically unstable, and moderate memory disorders are entirely female. Female elderly people who are depressed, psychologically unstable and having moderate memory disorder shall require supports and attention from family, Puskesmas (Pusat Kesehatan Masyarakat/Public Health Center), and local health department.